Long-Term Follow-Up Results of Fecal Microbiota Transplantation for Irritable Bowel Syndrome: A Single-Center, Retrospective Study - Cui, Jiaqu; Lin, Zhiliang; Tian, Hongliang; Yang, Bo; Zhao, Di; Ye, Chen; Li, Ning; Qin, Huanlong; Chen, Qiyi (Frontiers in Medicine, 2021)
Objective: This study aimed to investigate the long-term efficacy of fecal microbiota transplantation (FMT) in patients with irritable bowel syndrome (IBS). Study Methods: In this single-center long-term follow-up study, FMT treatment was administered to patients with moderate to severe IBS (IBS severity scoring system (IBS-SSS) > 175). After 1 year of treatment, it was decided whether to repeat FMT based on IBS-SSS score (IBS-SSS > 175). Baseline characteristics before and after FMT and questionnaires were completed at 1, 3, 6, 12, 24, 36, 48, and 60 months after FMT. The study outcomes included treatment efficacy rates, change of IBS-SSS, IBS-specific quality of life and fatigue, effect on stool frequency, Bristol Stool Scale for IBS-C and IBS-D, and side effects. Results: A total of 227 patients (47.58% IBS-C, 39.21% IBS-D, and 13.22% IBS-M) were recruited (142 females and 85 males with a mean age of 41.89 ± 13.57 years). The efficacy rates were 108 (51.92%), 147 (74.62%), 125 (74.41 %), 88 (71.54%), 78 (75.00%), 65 (73.03%), 45 (61.64%), and 37 (62.71%) at different follow-up time points. The total IBS-SSS score was 321.37 ± 73.89 before FMT, which significantly decreased after 1 month. The IBS-specific quality of life (IBS-QoL) score was 40.24 ± 11.34 before FMT, increased gradually, and was significantly higher at 3 months compared to before FMT. The total Fatigue Assessment Scale (FAS) score was 47 ± 8.64 before FMT and was significantly lower at 3 months. During follow-up, 89 (39.21%) side effects occurred that were alleviated by symptomatic treatment, and no serious adverse events were detected. Conclusion: Based on 60 months of long-term follow-up, the safety and efficacy of FMT for IBS was established. However, as the treatment effect declines over time, periodic and repetitive FMT is required for a sustained effect.